2019
DOI: 10.1002/cssc.201902443
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Activity of M−N4 Catalysts for the Oxygen Reduction Reaction by Electrolyte Adsorption

Abstract: Metal and nitrogen codoped carbons (M−N/Cs) have emerged as promising alternatives to platinum‐based catalysts for the oxygen reduction reaction (ORR). DFT calculations are used to investigate the adsorption of anions and impurities from the electrolyte on the active site, modeled as an M−N4 motif embedded in a planar carbon sheet (M=Cr, Mn, Fe, Co). The two‐dimensional catalyst structure implies that each metal atom has two potential active sites, one on each side of the sheet. Adsorption of anions or impurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
(144 reference statements)
3
26
0
Order By: Relevance
“…In contrast to operation in alkaline media, the presence of protons in acidic media makes it more challenging for the conversion of adsorbed O 2 into O 2 − (prior to the formation of OOH*). [ 31,32 ] Moreover, the coadsorption of ClO 4 − , Cl − , HCOO − , and SO 4 2− anions on the catalyst surface further slows the reaction in acidic compared to alkaline media, [ 31,33 ] which can be attributed to the physical blocking of the active sites by these adsorbents. These two limiting factors often result in a higher overpotential when the reaction is conducted in acidic rather than alkaline media.…”
Section: Challenges In Electrocatalyst Design For Renewable Energy Comentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to operation in alkaline media, the presence of protons in acidic media makes it more challenging for the conversion of adsorbed O 2 into O 2 − (prior to the formation of OOH*). [ 31,32 ] Moreover, the coadsorption of ClO 4 − , Cl − , HCOO − , and SO 4 2− anions on the catalyst surface further slows the reaction in acidic compared to alkaline media, [ 31,33 ] which can be attributed to the physical blocking of the active sites by these adsorbents. These two limiting factors often result in a higher overpotential when the reaction is conducted in acidic rather than alkaline media.…”
Section: Challenges In Electrocatalyst Design For Renewable Energy Comentioning
confidence: 99%
“…These two limiting factors often result in a higher overpotential when the reaction is conducted in acidic rather than alkaline media. [ 31–33 ] However, the adsorption of hydroxyl anions can optimize the free energies of intermediates during the reaction and thus improve ORR activity. [ 33 ] According to the Markovic principle, [ 31 ] the overpotential of the ORR increases as the electrolyte pH decreases.…”
Section: Challenges In Electrocatalyst Design For Renewable Energy Conversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar with the CoL, the adsorption strength for intermediates increases in the order of MnP<MnPc<MnNc. Since Mn‐based catalysts already possess excess strong adsorption strength, [17] strengthening adsorption significantly decreases the ORR activity of Mn complexes with the overpotential from 0.58 V for MnP to 1.22 V for MnNc. Same condition also occurs in Fe system since Fe‐based catalysts are located at the strong adsorption branch as similar as Mn‐based catalysts [18] .…”
Section: Figurementioning
confidence: 99%
“…[ 6 ] In spite of the enhancement of stability to a certain degree, the intrinsic structure of M‐N 4 ‐macrocycle would be destroyed during the high‐temperature calcination process, thus affecting the pristine fast electron transfer and weakening the activity. [ 6f,7 ] Recent studies demonstrated the substituents linked to the outer ring of macrocycles could regulate the electronic structure of the center metal atoms, making a significant difference in stability. [ 8 ] Meanwhile, FePc derivatives with functional groups and adjusted metal centers can also form polymers to achieve high stability.…”
Section: Introductionmentioning
confidence: 99%